Multi-level patterning nucleic acid photolithography - Kathrin Hölz (Nature Portfolio, 2019)
Increasing the complexity of engineered nucleic acid constructs and interfacing the microscopic with the macroscopic requires a multifaceted and programmable fabrication approach. Here the authors demonstrate multi-level photolithographic patterning for highly complex patterns at micrometer resolution.